Let's get lyrical. - Hancox, Dan (New Statesman, 2005)
Focuses on the use of similes in rap lyrics. Examples of similes used by Eminem, Pulp, 50 Cent, Wu-Tang Clan, Antipop Consortium, Fugees, Roll Deep Crew and other performers; Notion in the 18th and 19th centuries that writing poetry was fashionable for young men, according to Keats and Shelley; Details of the web site www.sonnets.org, which puts sonnets in competition with one another similar to rap battles.